KONFLIK ETNIS DAN PROBLEMATIKA MULTIKULTURALISME: ANALISIS TRAGEDI SAMPIT TERHADAP IMPLEMENTASI BHINNEKA TUNGGAL IKA - Aslan Noor; Bram Hasian Daniel Hutagalung; Dias Rahmah Aprilia; Keren Winfry Theresia; Qolbiyatuzzahro Qolbiyatuzzahro; Salsabila Putri Istnainy (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The 2001 Sampit Tragedy stands as one of the bloodiest ethnic conflicts in Indonesian history, marking a profound erosion of the value of Bhinneka Tunggal Ika (Unity in Diversity). This article aims to analyze the collapse of these pluralistic value, the correlation between structural inequality and the role of provocateurs, as well as post-conflict solutions grounded in local wisdom and Pancasila. This study employs a qualitative method with a library research approach, analyzing secondary data through sociological and anthropological perspectives. The findings reveal that the conflict between the Dayak and Madurese ethnic groups was not an isolated incident, but rather the culmination of latent tensions caused by the economic marginalization of indigenous communities, the failure of cultural acculturation, and the residual effects of the New Order's superficial security-oriented approach. The politicization of ethnic sentiment by provocateurs in the post-Reformasi era triggered an escalation of mass violence that claimed more than 500 lives and displaced approximately 100,000 residents. Post-conflict recovery was ultimately achieved through policy reconstruction and customary (adat) reconciliation. This study concludes that the management of diversity grounded in structural and legal justice is the primary key to safeguarding national integration.